JOB INSECURITY, WORKLOAD, AND TURNOVER INTENTION IN PT ENSEVAL PUTERA MEGATRADING - Aryandha, Pradita Nindya; Hidayati, Septi Nur (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
The study aims to determine the effect of job insecurity and workload both partially and simultaneously on turnover intention in employees of PT Enseval Putera Megatrading. The research was conducted at PT Enseval Putera Megatrading. This research is quantitative research with a total sample size of 124 people. Measurement uses a questionnaire with a Likert scale. The analysis technique used is the Simultaneous F test and partial t-test at the 0.05 significance level. The results concluded that there is a significant effect of job insecurity and workload both partially and simultaneously on turnover intention in employees of PT Enseval Putera Megatrading, with a p-value of 0.000 <0.05.